Redefinition Meaning of Tasawwuf in Contemporary Times - Mansurov, Fatkhiddin (Academy of Language Studies together with Academy of Contemporary Islamic Studies, Universiti Teknologi MARA Perak, 2016)
Tasawwuf is the purification of the heart from immoral habits in accordance with the will, to obtain eternal happiness and peace, to reach out to the level of maturation in morality through saving the heart from negative behaviour. Contemporary Muslim scholars consider reconstructing the definition of Tasawwuf and highlight it's essentiality for our life. Since monasticism was not the subject of classical Tasawwuf, there was no problem in its definition. According to them the goal of Tasawwuf is to live Islam with Ihsān, and join the community actively, share experience and knowledge, and help the others to encourage for establishing the peace in the society. In order to demystifying individuals who are internalizing the regulations of Tasawwuf, should be comprehended through the contemporary society in the World. The Muslim is someone who trusts, promises safety to his surrounding, and possess interrelated colourful differences in harmony. He evaluates him based on contributions to the well beings of others. His concentration is always on ‘We’ rather than ‘I’. In this description, the Muslims become a negotiator of ‘positive action’ and nothing can prevent him from acting and contributing to the community positively. In this study we are going to re-define the meaning of spiritual life in accordance with the Qur’an and Sunnah, and identify the problems of misunderstandings and practices of Tasawwuf.